Radiation-induced phase separation in nanostructured Hf-In-C ternary thin films under irradiation with 200 keV Ar+ ion beam. Issue 1 (1st February 2022) - Vacik, Jiri; Cannavò, Antonino; Bakardjieva, Snejana; Kupcik, Jaroslav; Lavrentiev, Vasily; Ceccio, Giovanni; Horak, Pavel; Nemecek, Jiri; Verna, Alessio; Parmeggiani, Matteo; Calcagno, Lucia; Klie, Robert; et al.
Abstract : Thin films consisting of 17 groups of Hf/In/C multilayers cyclically alternating layers of Hf, In and C each with a thickness of 4–5 nm were synthesized by ion sputtering using a 25 keV Ar + ion beam with 400 µA current and targets made of pure hafnium, indium and carbon. The films were subsequently annealed in vacuum at 120°C for 24 hours to induce intermixing of elements phases, their interaction, and formation of the Hf-In-C nanostructures (including the Hf2 InC MAX phase). After fabrication, a part of the pristine (as deposited) samples was irradiated by 200 keV Ar + ions at high fluences 10 15 and 10 17 cm −2 . Both samples (as prepared and irradiated) were analyzed by IBA nuclear analytical methods, as well as by AFM and TEM microscopic techniques, and by XPS and profilometry to understand the microstructural evolution. Moreover, nanoindentation analysis was performed to assess the effects of ion irradiation on the microstructure and mechanical properties of the films. The experimental results showed that thin Hf-In-C nanostructured films can be formed by ion sputtering with promising mechanical parameters. The irradiated Hf-In-C films were found to be resistant only up to a fluence of about 10 15 Ar cm −2 . At higher fluences it degrades, and Hf2 InC transforms to the binary HfC0 . 95 phase due to sublimation of In. At 10 17 cm −2 the original matrix (including M2 AX) is destroyed, and instead, a mixture of MX binary phases ( e.g. HfC0 . 95 ) and crystalline oxides ( e.g. HfO2 and In2 O3 ) are formed.